IMPLEMENTASI MODEL PEMBELAJARAN âCERDASâ BERBASIS TEORI MULTIPLE INTELLIGENCES (MI) DALAM PEMBELAJARAN IPA - Winarti, Atiek (Vidya Karya Jurnal Kependidikan, 2013)
This study aims to develop a model of learning â CERDAS â -based on Multiple Intelligences ( MI ) theory. The syntax consists of six stages which are Cermin DiriÂ  (SelfÂ  mirror), Ekspose konsep (concept exposure),Â Â  Rumuskan Keingintahuan (curiosity formulation),Â  Dalami konsep (understood better the concept ), Akui Bakat (talent admission) and Simpul Ingatan (memory node). The effectiveness of the model seen from the model âs ability to develop studentsâ intelligence , adherence to the model , as well as science learning outcomes ofÂ  students in junior high school. The research uses R & D design consited ofÂ  several stagesÂ  namely problem identification, design models, design validation , design revisions, limited evaluation and revision of design based on the evaluation results. The development of learning devices based on the steps of Dick & Carey (2009). Validation of the model is conducted by five experts. The design of learning modelÂ  was tried out on a limited scale by applying an explanatory design with experimental design One - Group Pretest - Posttest Design at SMPN1 Banjarmasin. Validation sheetÂ  of learning device, observation sheets of learning implementation and student activity,Â  Multiple Intelligence Test developed by Armstrong (2004), as well as achievement test are used as research instrument. The data analysis uses qualitative descriptive techniques and t test. Based on the results of this study is concluded that (1) âCERDASâ model feasible for use as a model forÂ  developing multiple intelligences, improving student process skills and learning outcomes through syntax Self Mirror, Exposure concept, Formulate Curiosity , understood better the concept , Admit Talent and Memory Node. (2) Implementation ofÂ  âCERDASâ model develops multiple intelligences, science process skills, and concept mastery of the students. (3) Students give very goodÂ  respon for the model, especially for lab activities , application of process skills and talents Admit syntax.